When Opposite Attract: An Exploratory Study of the Relationship between Entrepreneurial Orientation and Market Orientation and their Paths to Innovation and Performance - Yip, Leslie Ka Wa (2006)
A central challenge facing firms is their ability to innovate and create new products whilst at the same time meeting existing market demands. Entrepreneurial orientation has been proposed as a solution to the former whilst market orientation is proposed as a solution to the latter. Entrepreneurial orientation is a mindset a firm can employ to encourage innovative and creative activity designed to create products in anticipation of future market trends. Market orientation is a set of behaviours associated with collecting, disseminating and responding to information on current customers and market needs. Recent research has suggested that a firm should use both orientations to ensure it does not become market-led but is instead market-leading with its current and future products. However, studies into the simultaneous use of EO and MO have reported tensions between the two orientations such that they may be compatible. This problem is compounded by contradictory research findings which imply that we are yet to fully understand how the two work together in practice. In this study, a thorough analysis is made of literature into the relationship between the two orientations and a conceptual model is developed specifying how the two can be made to work in practice and what their outcomes are likely to be. This model is then explored using two case studies: BMW and Toyota. It is found that EO, MO, and EO and MO in conjunction are all different paths to superior performance but each path bears very different characteristics and implications for the type of learning and the type of innovation. Implications for academics, managers, and public policy are highlighted as well as avenues for future research. Study limitations are also acknowledged.